MODERNISASI PEMBELAJARAN AGAMA ISLAM PESANTREN JAGAT ARSY SEBAGAI RESPON TERHADAP REVOLUSI INDUSTRI 4.0 - Muhammad Abduh; Syahlarriyadi (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2023)
Pesantren are one of the oldest institutions of education and are unique in Nusantara, Indonesia. Islamic Religious Education (PAI) is the spirit and core of learning in Pesantren. In the industrial era 4.0, humans are required to be familiar with technology and people are required to think critically, constructively and innovatively. Islamic Religious Education is a medium for expressing thoughts, ideas, ideas and feelings that can shape the behavior of learning communities. Pesantren Jagat Arsy is one of the Educational Institutions that adapts to this progress. The purpose of this writing is to find out how far the modernization of Pesantren applies Islamic education learning planning in the 4.0 era. then explained about the various kinds of innovations in PAI learning, and explained about the benefits and how to apply PAI learning in the Industry 4.0 era. The research method used was library research and field observations. It was found that the modernization of PAI learning in the Industry 4.0 era is an advantage, it is even very important to use it by utilizing various information technology-based learning applications. In this case, it can be concluded that the important factors in planning PAI learning in the Industry 4.0 era are mastery of information technology and learning innovation. So that Pesantren are able to respond and modernize PAI learning by utilizing various digital platforms related to education. Pesantren must be able to respond to the modernization of PAI learning in the industrial era 4.0 by changing the educational paradigm to be more modern and able to respond to the times, with various policy adjustments